Genicular Nerve Radiofrequency Ablation for Chronic Knee Pain Using a Three-Tined Electrode: A Technical Description and Case Series. Issue 12 (27th September 2020) - Koshi, Edvin; Cheney, Cole W; Sperry, Beau P; Conger, Aaron; McCormick, Zachary L
Abstract: Background: Genicular nerve radiofrequency ablation (RFA) for the treatment of chronic knee pain has traditionally targeted the superomedial, superolateral, and inferomedial genicular nerves. However, recent cadaveric studies of knee neuroanatomy demonstrate varied locations of these specific nerves as well as additional articular nerves. This work suggests that traditional genicular nerve RFA lesion locations may be inadequate. Objective: 1) To describe a novel protocol utilizing a three-tined RFA electrode to target the superomedial (SMGN), superolateral (SLGN), and inferomedial genicular nerves (IMGN), as well as the terminal articular branches of the nerves to the vastus medialis (NVM), intermedius (NVI), and lateralis (NVL). 2) To assess the ability of this technique to reduce chronic knee pain. Methods: Case series of consecutive patients with six or more months of refractory knee pain who underwent genicular nerve RFA according to the novel protocol described. Seven discrete RFA lesions were placed to target the SMGN, NVM, NVI, NVL, SLGN, and IGMN. Results: Eleven patients underwent RFA, nine with knee osteoarthritis and two postarthroplasty. At one month, 91% (95% CI = 59–100%), 82% (95% CI = 48–98%), and 9% (95% CI = 2–41%), of patients reported ≥50%, ≥80%, and 100% improvement in knee pain on the numeric rating scale, respectively. These results were sustained at six months. There were no complications. Discussion/Conclusions: These preliminary data suggest the feasibility and possible effectiveness of genicular nerve RFA using the described novel protocol including a three-tined electrode. Larger-scale studies with comparative groups are warranted.